MODEL ADOPSI BAGI KELUARGA YANG TIDAK MEMPUNYAI ANAK DALAM MEMPERTAHANKAN PERKAWINAN DI DESA KECURIT TOHO - Adel, Bertus; Rustiyarso, Rustiyarso; Zakso, Amrazi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe problem in this study is how the adoption model for families who have no children in maintaining marriage. The purpose of this study was to describe the adoption model used by families who have no children in maintaining marriage. This research uses qualitative approach with in-depth interview method. The location of this research was conducted in Kecurit Village Toho, informants in this study were married couples who have adopted children who numbered six heads of families. The tools used in collecting research data are used observation guides, interview guides and documentation guides. Based on the results of research and discussion in the research the authors conclude that the entire informant using the adoption model of culture approach with the process done in a familial. This is evidenced from the findings of the field based on two sub-problems as follows: 1) The adoption process of children by adoptive parents using the procedure or the adoption process in a closed or done under the hands of a familial approach. The steps adopted by adoptive parents adopt simple adoption by visiting the immediate family of adoptive adopted parents parents, after agreeing to the provision of reimbursement of hospital maternity fees, and the agreement of both parties is only done orally with confidence and mutual believe; 2) The responsibilities and obligations of adoptive adoptive parents fulfill responsibilities well this is evidenced by the excellent care of the child, caring for him painstakingly, loving him more than any other biological parent who normally possesses the child and educates to adulthood.Â Keywords: Adoption Model, Families do not Have Children, Maintaining Marriage